Productivity of FAD-Based Purse Seine Fisheries and Its Relationship with Oceanographic Variability in the Makassar Strait (Torani Journal of Fisheries and Marine Science, 2026)
The Makassar Strait is one of Indonesia’s productive fishing grounds and serves as an important operational area for FAD-associated purse seine fisheries. The productivity of pelagic fisheries in this region is influenced by the use of fish aggregating devices (FADs) and oceanographic conditions that affect fish distribution and abundance. This study aimed to analyze catch composition, estimate fishing productivity using Catch Per Unit Effort (CPUE), and examine its relationship with oceanographic parameters in the Makassar Strait. The research was conducted from September to November 2025 at the Lero Fish Landing Base (PPI Lero), Pinrang Regency, South Sulawesi. Primary data were collected through field observations, catch recording, fishing-trip monitoring, and fishing ground. Oceanographic data, including sea surface temperature (SST), chlorophyll-a, salinity, and current velocity, were obtained from MODIS satellite imagery and the Copernicus Marine Data Store. Data were analyzed descriptively for catch composition, while CPUE was used to evaluate fishing productivity and its association with oceanographic variables. The results showed that the catch was dominated by skipjack tuna (Katsuwonus pelamis), kawakawa (Euthynnus affinis), and scads (Decapterus spp.). Total catch reached 48,638 kg from 17 fishing trips, resulting in a CPUE value of 2,861.06 kg trip⁻¹. The highest catches were associated with SST of 30.6–30.8°C, salinity of 33.80–33.89 ppt, chlorophyll-a concentrations of 0.13–0.19 mg m⁻³, and current velocities of 0.85–1.04 m s⁻¹. These findings indicate that purse seine productivity is influenced by the interaction between FAD deployment and favorable oceanographic conditions that support pelagic fish aggregation.
Keywords: Catch Per Unit Effort (CPUE); Purse Seine; fish aggregating devices (FADs); Oceanographic Paramaters; Makassar Strait